Beyond Asexual: Genomics-Driven Progress in Unveiling Sexual Reproduction in Cereal Rust Fungi - Shideh Mojerlou; Mareike Moeller; Benjamin Schwessinger; Julian Rodriguez-Algaba (Molecular Plant-Microbe Interactions)
Recent advances in genomics technologies have revolutionized our understanding of cereal rust fungi, providing unprecedented insights into the complexities of their sexual life cycle. Genomic approaches, including long-read sequencing, genome assembly, and haplotype phasing technologies, have revealed critical insights into mating systems, genetic diversity, virulence evolution, and host adaptation. Population genomics studies have uncovered diverse reproductive strategies across different cereal rust species and geographic regions, highlighting the interplay between sexual recombination and asexual reproduction. Transcriptomics have begun to unravel the gene expression networks driving sexual reproduction, and complementary omics approaches such as proteomics and metabolomics offer potential insights into the underlying molecular processes. Despite this progress, many aspects of cereal rust sexual reproduction remain elusive. Integrating multiple omics approaches with advanced cell biology techniques can help address these knowledge gaps, particularly in understanding sexual reproduction and its role in pathogen evolution. This comprehensive approach will be crucial for developing more targeted and resilient crop protection strategies, ultimately contributing to global food security. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY 4.0 International license.